Chemical and Microbiological Characteristics of Sei-Pindang Tuna Fish - I Gde Suranaya Pandit; Pande Ayu Naya Kasih Permatananda; I Nengah Suaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pindang is a fishery processing product that plays an important role in post-harvest activities. Pindang products have a relatively short shelf life, namely less than 2 days at room temperature. Smoking is a drying technique used to maintain the shelf life of fish by using wood fuel as a smoke producer. Pindang tuna that has undergone the smoking process is given the name Sei-Pindang Ikan Tongkol. The aim of this research is to determine the chemical and microbiological characteristics of Sei-Pindang Tuna Fish. The results showed that sei-pindang tuna had a water content of 44.69 ± 0.66%, histamine content of 11.88 ± 1.12 mg N/100 g, total volatile bases content of 43.23 ± 0.22 mg N/100 g and the total number of bacteria was 2.1 x104 ± 1.2 x103 cfu/g.